A systems design improvement study on YDG Coffee - Baluyot, Mikael Konrad B.; Cuenca, Crescent O.; Delos Reyes, Jason S.; Jazmines, Ma, Sophia Adriel E.
With the advancements in technology, people's way of life changed. Because of a now convenience-driven lifestyle, more people rely on the convenience offered by fast food chains and establishments which offer takeout and delivery services. This study focuses on improving YDG Coffee's service, particularly the takeout service time. Being surrounded by a lot of business establishments, YDG Coffee's potential customers are people who would want food served in the fastest time possible so they could still spend their breaks resting or doing other activities for leisure. YDG Coffee is a company established by young Filipinos who have a vision of "providing people good coffee without the BS". They feel they have a mission to "uplift daily life through Specialty Coffee, good music, and a lot of good vibes". Aside from their coffee, YDG Coffee also serves breakfast meals, pasta, sandwiches, desserts and other drinks. Currently, there is no definite management structure and job distribution within the company. It is being managed by four owners who run the company in an unconventional way, that is , they visit the shop whenever they can and occassionally help the staff in accommodating customers. The shop opens at 8:00AM and closes at 10:00 PM, with five staff members fulfilling 8-hour shifts each. The owners have good relations with the shop's raw materials suppliers so lead time is just 1-day. Equipment has backups so no downtime is really experienced. For their inventory and sales reports, YDG Coffee utilizes Square Point of Sale. The study only covers the store's peak hours which is 11:00AM to 2:00PM and an additional data coverage of 2:00 to 4:00PM. Aside from this, the analysis of product lead time was only limited to the data from CCTV footages provided by the building's security company. The study utilizes data from the company's Square-POS acccount in all analysis relating to finances. However, due to data confidentiality, the cost of production is not available so revenue is the focus of study. Of all YDG Coffee's items, the study focuses only on breakfast meals, pasta, sandwiches and drinks consisting of coffee and non-coffee beverages. This is because sales from these categories have the highest contribution. Upon initial time study, it was observed that breakfast meals, pasta and sandwiches needs the same preparation time per gram of item so the categories are further narrowed down into two: food and drinks. Due to the company's location, being in Mandaluyong, the whole Metro Manila population is considered as potential customers. Aside from this, the system is assumed to operate at its maximum capacity during its peak hours so all orders during this period are takeouts. The sample size needed for the survey was first computed using Slovin's Formula. Then a survey about takeout orders was conducted which gave customers' ideal waiting time for the food and drink they ordered for takeout. A time study was performed to determine the current service times fo YDG Coffee for takeout of food and drinks. Comparison of values from the survey and time study suggests that the establishment could not keep up to the expected service times of customers, causing possible loss of potential and repeating customers. Analysis of the problem leads to the unsatisfactory staff performance as the main cause. The possible causes of unsatisfactory staff performance have been arranged into problem clusters where it would be easier for the problem to be addressed. The problem clusters are Inconsistent Managerial Presence, Lack of Time Standards and Unergonomic Layout, and Lack of Initial Training. Solving these subproblems could improve staff performance, thereby solving the problem with service time. Promotion of an employee to supervisor was selected as alternative to Inconsistent Managerial Presence which will incur a cost of Php 4,640 due to the increase in wage of the employee. Lack of Time Standards and Unergonomic Layout was addressed by establishment of standard time and leveling of equipment and materials which will incur a cost of Php 12, 163.30. Lastly, both creation of employee handbook and constant reviews and refresher courses are chosen to solve issues related to Lack of Initial Training which will incur a production cost of Php 300 for two copie of Employee Handbook. The cost of all proposed alternatives is Php 17,103.30. If implemented, the study could lead to an increase of Php 5,322.49 and Ph 15,692.31 in monthly sales of takeout food and drinks respectively. With a total increase in takeout orders annual sales of Php 252,177.60, sales outweighs the total cost of implementation of the proposed alternatives.